Fatores associados à presença da cintura hipertrigliceridêmica em mulheres hipertensas e com excesso de peso - Santos, Sieune Roberta Araújo Gomes dos (2016)
The metabolic triad, characterized by fasting hyperinsulinemia, hiperapoliproteína B and high proportion of dense and small particles of LDL, can predict cardiovascular risk and is strongly correlated to the marker hypertriglyceridemic waist (HW). The HW defined as the simultaneous presence of increased waist circumference (WC) associated with high levels of triglycerides (TG), it has been presented as a screening marker for the characterization of individuals of this triad. Cross-sectional study was conducted at the University Hospital of the Nutrition Clinic at the Federal University of Sergipe, including women with overweight, hypertension and aged ≥ 18 years and excluding pregnant women and / or living with HIV, cancer and kidney diseases. Sampling was simple random and without replacement through the list of women treated at the clinic. The limiting points for the diagnosis of HW followed the criteria adopted by NCPET-ATP III (National Cholesterol Evaluation Program for Adult Treatment Panel III) for women: CC ≥88 cm and TG ≥ 150 mg / dL. The prevalence ratios and their 95% confidence intervals were estimated. To identify factors associated with HW was used the logistic regression model. The significance level was 5%. The presence of HW was frequently seen in woman that smoked (PR: 1.74; p = 0.003) and for woman with higher Framingham scores (p < 0.001). These woman also presented age (p = 0.001) and biochemical parameters more elevated, such as glycemia (p = 0.001) and total cholesterol (p = 0.007) and HDL (p < 0.001). After multivariate regression analysis, the variables resulting from the final model were glycemia (p = 0.0242), total cholesterol (p = 0.0004), HDL (p = 0.0007), age (p =0.0324) and smoking habits (p = 0.0218). The factors associated significantly to the presence of hypertriglyceridemic waist in the samples studied were those considered of cardiometabolic risk: fasting hyperglycemia, hypercholesterolemia and low serum levels of HDL. Besides significant association of HW to Framingham score, age and smoking habits.